ANALISA GAMBARAN EFISIENSI PELAYANAN RAWAT INAP BERDASARKAN GRAFIK BARBER JOHNSON DI RS MATERNA MEDAN PERIODE TRIWULAN - AMINI, RINI SRI (LP2MTBM MAKARIOZ, 2021)
One of the indicators that hospitals must pay attention to improve hospital services is the efficiency of inpatient services, especially bed utilization. The number of beds used in inpatient services influences the level of efficiency of bed use in the hospital. One of the activities routinely carried out in hospital statistics is calculating the level of bed use efficiency (TT). It is said that efficiency is seen from two aspects, namely from a medical perspective reviewing efficiency from the quality of medical services and from an economic perspective reviewing efficiency from the perspective of utilizing existing facilities and infrastructure. There are four parameters to monitor and assess the level of efficiency of bed use for patient care wards. One of the activities routinely carried out in hospital statistics is calculating the level of bed use efficiency (TT). It is said that efficiency is viewed from two aspects, namely from a medical perspective reviewing efficiency from the quality of medical services and from an economic perspective reviewing efficiency from the perspective of utilizing existing facilities and infrastructure. There are four parameters to monitor and assess the level of efficiency of bed use for patient care wards.